Blended and Hybrid Learning Initiatives: A curated list for El Salvador - Villavicencio, Xuzel; Coflan, Caitlin Moss (EdTech Hub, 2022)
This document was produced in response to a request from the UNICEF country office and Ministry of Education team of El Salvador that was submitted to the EdTech Hub Helpdesk in November 2021. The UNICEF team requested a curated list of global blended and hybrid initiatives with a focus on initiatives that have used a multimodal strategy, highlighting effective and ineffective practices. This report does not aim to cover every leading and innovative blended / hybrid initiative with relevance to the Salvadoran context. Rather, it presents a list of curated resources with examples of challenges, lessons learned, and teacher training approaches that can be used as a guide when designing a multimodal strategy for the education sector. Keywords: hybrid; blended; El Salvador; multimodal; teacher training; remote learning An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Mapping and Analysing Digital Learning Platforms in Latin America and the Caribbean - Myers, Christina; Wyss, Natalie; Villavicencio Peralta, Xuzel; Coflan, Caitlin (EdTech Hub, 2022)
This document was produced in response to a request from the UNICEF Latin America and Caribbean Regional Office (LACRO) submitted to the EdTech Hub Helpdesk in October 2021. The UNICEF team requested a curated list of digital learning platforms in the Latin America and Caribbean (LAC) region and an analysis of a shortlisted series of platforms intending to explore their potential for at-scale implementation and impact. This report does not aim to cover every leading and innovative digital learning platform in the LAC region. Rather, it presents a list of promising platforms and discusses their design and implementation to explore their relevance and potential for at-scale impact. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Minoritised Languages, Education, and Technology: Current practices and future directions in low- and middle-income countries - Zhao, Annette; Mitchell, Joel; Gasanabandi, Gentille; Ullah, Noor; Barnes, Katrina; Koomar, Saalim (EdTech Hub, 2024)
This article explores the current status and future directions of mother-tongue-based multilingual education (MTB MLE) and the use of technology in low- and middle-income countries (LMICs), focusing on the use of minoritised mother tongues. An initial literature review of available academic sources in multiple languages reveals a lack of evidence on the use of technology in MTB MLE across different countries, especially multilingual contexts with greater linguistic diversity. To understand the issue in greater detail and to offer recommendations informed by current practice, interviews and a collaborative workshop with four organisations with relevant educational technology (EdTech) initiatives were conducted. The analysis covers facilitating and limiting factors these organisations have encountered, and the potential positive impact on learners and society generally. We conclude by identifying practical, policy, and research priorities for multilingual education and educational technology in general.
Keywords: _r:AddedByZotZen